Petras Vileišis (1851–1926) as the Pioneer in creating Lithuanian “Arithmetic” - Banionis, Juozas (Lietuvos matematikos rinkinys, 2009)
Petras Vileišis (1851–1926) is one of the most prominent Lithuanian personalities at the end of the 19th c. and the beginning of the 20th c., who was distinguished for his universal activity. He is mostly well known as an engineer, a man in culture, a public man, a promoter of Lithuanianism. However, Petras Vileišis’s merit in the development of Lithuanian mathematical education is underestimated. The article throws the light on the circumstances of creating “Arithmetic” by a diplomaed mathematician P. Nėrys (P. Vileišis), its content and the importance for mathematical education in Lithuania.